Implementação de gerenciamento de serviços de telecomunicações utilizando CORBA, java e reflexão computacional - Sobral, Joao Bosco Mangueira (2001)
Currently, the telecommunications management systems are powerful, however, maintain centralized and proprietary platforms, limiting this way, the growth of these telecommunications networks. This factor generates the need for scalable and open systems, stimulating the sectors of the telecommunications area to seek for solutions for the problem in distributed, heterogeneous and totally scalable environments. The recent advances in the area of distributed objects, has created many positive expectations for the development of client/server systems which use, as if they were local, resources available through the network. This way, the objective of this work consists in the experimental evaluation of the potential of the main CORBA services in conjunction with the Java language, through the necessary requirements for the main functionalities proposed by the TMN architecture. For the implementation of the telecommunication services with the reusability of codes we use computational refection with meta-classes substituting the manager and classes substituting the agents.